If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + 9 = 35 Reorder the terms: 9 + 2u = 35 Solving 9 + 2u = 35 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2u = 35 + -9 Combine like terms: 9 + -9 = 0 0 + 2u = 35 + -9 2u = 35 + -9 Combine like terms: 35 + -9 = 26 2u = 26 Divide each side by '2'. u = 13 Simplifying u = 13
| 3p-2(5p+10)=7(p-2)+9 | | 8b+6b-14=8+2b+2 | | (4+2x)/4=2(x+5) | | -46+6-4=3 | | logx=0.6990 | | 0.4y=78+4y | | 2x/5-1=x/4+2 | | 9x+2x-x=200 | | .45/76=x/60 | | Y/36=3/4 | | 4x+x(4)=88 | | 3/5y=27 | | 6(x+6)=72 | | -2+4v=-14 | | 110+87+100=180 | | 6+2(x+10)=60 | | 4(-3)-5y=-7 | | -7=w-9 | | 4x+13=x+22 | | 2+u=8 | | x^3+3x^2-11=0 | | 3x-4(3x-2)=7x-2/3+1/2-x/5 | | 5x-5(x+10)=100 | | 3x+5x-8=20 | | 8x-116=4x-8 | | 4+4log(x)=5 | | 10(x+10)=180 | | 5(2x-7)=3-8x+2 | | 0.3x-9+2x=4x-3 | | R+(R*1.5)=25 | | 4x+9=4(x+4)-7 | | (x^2)+24=8(x+1) |